2013
DOI: 10.1371/journal.pone.0081369
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Age, Parity and Isolated Birth Defects: A Population-Based Case-Control Study in Shenzhen, China

Abstract: BackgroundThe etiology of birth defects has been widely studied but is not yet fully clarified, previously published data had suggested that maternal age or parity maybe involved, but without consistent conclusions.MethodsA population-based, case-control study was nested in a cohort of perinatal infants born from 2010 to 2012 in Baoan District, Shenzhen. Four categories of isolated birth defects were defined as cases: congenital heart defects (CHD, n = 693), polydactyly (n = 352), cleft lip with or without pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 20 publications
2
40
2
2
Order By: Relevance
“…In the present study, we found no association between maternal age and clefts (p=0.747). A previous meta-analysis study 16 showed that the probability of mothers aged between 35 and 39 years having a child with cleft palate was 20% higher in comparison with those between 20 and 29 years old. For mothers aged 40 years or older, this probability was 28% higher compared to those aged between 20 and 29 years old.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In the present study, we found no association between maternal age and clefts (p=0.747). A previous meta-analysis study 16 showed that the probability of mothers aged between 35 and 39 years having a child with cleft palate was 20% higher in comparison with those between 20 and 29 years old. For mothers aged 40 years or older, this probability was 28% higher compared to those aged between 20 and 29 years old.…”
Section: Resultsmentioning
confidence: 96%
“…To understand the developmental mechanisms underlying NSCL/P, it is essential to review a large and varied field of research 14 . The environmental risk factors for NSCL/P include maternal use of medications such as antiepileptic agents or corticosteroids, smoking and alcohol consumption during pregnancy 15 , intrapartum interval 10 , parity 16 , folic acid deficiencies 17 and maternal and paternal age 5 . However, there is no consensus on the association of parental age and NSCL/P 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, twin and multi-fetal infants were positively associated with the increased risk of congenital heart disease. It was commonly considered that an excessive number of parturitions may lead to reproductive organ damage and dysfunction and increase the risk of CHD [24]. Further studies will be required to corroborate these findings and, if confirmed, to elucidate possible reasons for these associations.…”
Section: Discussionmentioning
confidence: 96%
“…The proportion of mothers over 35 years of age at the time of delivery in Murmansk County was 5.7%, while it was 16.7% in Norway [10]. Advanced maternal age is significantly associated with an increased risk for a variety of birth defects [26], including those of the heart and Down syndrome [27]. In our study, the prevalence of these two defects was lower in Murmansk County than in Norway, which likely reflects the lower average maternal age observed in Murmansk County.…”
Section: Discussionmentioning
confidence: 99%